2018
DOI: 10.1136/bmjopen-2018-023166
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a German multicentre healthcare research study: a survey of research personnels’ attitudes, experiences and work load

Abstract: ObjectivesThe DACAPO study as a multicentre nationwide observational healthcare research study investigates the influence of quality of care on the quality of life in patients with acute respiratory distress syndrome. The aim of this study was to investigate the acceptability to the participating research personnels by assessing attitudes, experiences and workload associated with the conduct of the DACAPO study.Design, setting and participantsA prospective anonymous online survey was sent via email account to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…ICU nurses are often interested in participating in clinical research, but they lack time, money and support from peers and management (Al‐Dorzi, Naidu, Khokhar, White, & Arabi, ; Blecha et al, ; Smith, Dale, Mehta, Pinto, & Rose, ). ICU nurses often have a pivotal role in research as data collectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICU nurses are often interested in participating in clinical research, but they lack time, money and support from peers and management (Al‐Dorzi, Naidu, Khokhar, White, & Arabi, ; Blecha et al, ; Smith, Dale, Mehta, Pinto, & Rose, ). ICU nurses often have a pivotal role in research as data collectors.…”
Section: Introductionmentioning
confidence: 99%
“…However, a Swedish qualitative study (n = 8) showed that nurses valued patient feedback positively, although patients generally had little recall of their ICU stay (Engstrom & Soderberg, 2010). ICU nurses are often interested in participating in clinical research, but they lack time, money and support from peers and management (Al-Dorzi, Naidu, Khokhar, White, & Arabi, 2013;Blecha et al, 2018;Smith, Dale, Mehta, Pinto, & Rose, 2016). ICU nurses often have a pivotal role in research as data collectors.…”
Section: Introductionmentioning
confidence: 99%